Context Matters for Social‐Emotional Learning: Examining Variation in Program Impact by Dimensions of School Climate. Issue 1 (23rd June 2015) - McCormick, Meghan P.; Cappella, Elise; O'Connor, Erin E.; McClowry, Sandee G.
Abstract: This paper examines whether three dimensions of school climate—leadership, accountability, and safety/respect—moderated the impacts of the INSIGHTS program on students' social‐emotional, behavioral, and academic outcomes. Twenty‐two urban schools and N = 435 low‐income racial/ethnic minority students were enrolled in the study and received intervention services across the course of 2 years, in both kindergarten and first grade. Intervention effects on math and reading achievement were larger for students enrolled in schools with lower overall levels of leadership, accountability, and safety/respect at baseline. Program impacts on disruptive behaviors were greater in schools with lower levels of accountability at baseline; impacts on sustained attention were greater in schools with lower levels of safety/respect at baseline. Implications for Social‐Emotional Learning program implementation, replication, and scale‐up are discussed.